Respostas
respondido por:
1
Primeiro encontrar a razão:
Razão = a2 - a1
r= a2 - a1
r = 2 - 5
r = -3
======
Encontrar o valor de a10
an = a1 + ( n -1 ) * r
a10 = 5 + ( 10 -1 )* ( -3 )
a10 = 5 + ( 9 ) * -3
a10 = 5 - 27
a10 = -22
====
Soma dos termos:
Sn = ( a1 + an ) * n / 2
Sn = ( 5 - 22 ) * 10 / 2
Sn = -17 * 5
Sn = -85
Som dos 10 primeiros termos = -85
Razão = a2 - a1
r= a2 - a1
r = 2 - 5
r = -3
======
Encontrar o valor de a10
an = a1 + ( n -1 ) * r
a10 = 5 + ( 10 -1 )* ( -3 )
a10 = 5 + ( 9 ) * -3
a10 = 5 - 27
a10 = -22
====
Soma dos termos:
Sn = ( a1 + an ) * n / 2
Sn = ( 5 - 22 ) * 10 / 2
Sn = -17 * 5
Sn = -85
Som dos 10 primeiros termos = -85
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás